Respiratory infections and nutritional deficiencies in Chadian children under five years between 1990 to 2021: Incidence, DALYs, risk factors and policies performance - Nodjimadji T Martial; Neguemadji N Ngaba; Sweetyben Patel; Lidya Metekia; Imteyaz A Khan; Amit Gulati; Sakshi Khurana; Ousmane A Mahamat (Journal of Global Health Economics and Policy)
# Background The burden of lower respiratory infections (LRI), upper respiratory infections (URI), and nutritional deficiencies (ND) among children under five in low-income countries has remained critically high for decades. # Methods Data, expressed as rates per 100,000 people from the Global Burden of Diseases, were analyzed to investigate trends, maternal risk factors, and the performance of health policies related to LRI, URI, and ND incidence as well as disability-adjusted life years (DALYs) in Chadian children under five. # Findings Over the study period, LRI and ND incidence declined in boys and girls under five. Additionally, DALYs from LRI, URI, and ND all exhibited decreasing trends. Moreover, an increase in the maternal prevalence of gynecological diseases, maternal disorders, HIV/AIDS, tuberculosis, nutritional deficiencies, malaria, alcohol use disorders, and hepatitis B was associated with an increase in the incidence and DALYs of LRI, URI, and ND in children under five. Consequently, the policies enacted in Chad since 2015 to improve children’s health resulted only in the decline in LRI incidence and DALYs, as well as ND incidence. # Conclusions URI incidence in Chadian children under five requires particular attention. Furthermore, many maternal health conditions have been identified as being associated with the incidence and DALYs of LRI, URI, and ND. Since existing policies did not effectively decrease the incidence and DALYs of all three conditions, implementing specific policies targeting URI and maternal health might substantially alleviate the burden of respiratory infections and ND in children under five in low-income countries such as Chad.